A Redox‐Activated G‐Quadruplex DNA Binder Based on a Platinum(IV)–Salphen Complex. Issue 1 (7th December 2017) - Bandeira, Stephane; Gonzalez‐Garcia, Jorge; Pensa, Evangelina; Albrecht, Tim; Vilar, Ramon
Abstract: There has been increasing interest in the development of small molecules that can selectively bind to G‐quadruplex DNA structures. The latter have been associated with a number of key biological processes and therefore are proposed to be potential targets for drug development. Herein, we report the first example of a reduction‐activated G‐quadruplex DNA binder. We show that a new octahedral platinum(IV)–salphen complex does not interact with DNA in aqueous media at pH 7.4; however, upon addition of bioreductants such as ascorbic acid or glutathione, the compound is readily reduced to the corresponding square planar platinum(II) complex. In contrast to the parent platinum(IV) complex, the in situ generated platinum(II) complex has good affinity for G‐quadruplex DNA. Abstract : Be there and be square : A reduction‐activated G‐quadruplex DNA binder is reported. The new octahedral platinum(IV)–salphen complex does not interact with DNA in aqueous media at pH 7.4. However, upon addition of bioreductants such as ascorbic acid or glutathione, the compound is readily reduced to the corresponding square planar platinum(II) complex, which binds to G‐quadruplex DNA with high affinity.